2021
DOI: 10.1111/jpc.15395
|View full text |Cite
|
Sign up to set email alerts
|

Hand sanitiser‐associated ocular chemical injury in children

Abstract: Hand hygiene using hand sanitisers which contain at least 60% alcohol has been advised 1 to prevent the transmission of Covid-19. To date, most hand sanitisers contain alcohol-based formulations with 62-95% alcohol, which denature proteins and have the ability to inactivate viruses. 2 Amid the Covid-19 pandemic, an increase of ocular chemical injuries associated with hand sanitisers has been reported. 3 Several children have presented at our ophthalmology emergency department because of ocular injuries caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[ 16 ] Our study revealed an increase in the proportion of chemical injuries partly due to an increased number of sanitizer-related ocular injuries rather than occupation related, in keeping with recent reports in the literature. [ 17 18 ] Interesting to note, there was a significant increase in dry eye syndrome. It is hypothesized that patients under lockdown are at risk of ocular surface alterations due to a number of predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Our study revealed an increase in the proportion of chemical injuries partly due to an increased number of sanitizer-related ocular injuries rather than occupation related, in keeping with recent reports in the literature. [ 17 18 ] Interesting to note, there was a significant increase in dry eye syndrome. It is hypothesized that patients under lockdown are at risk of ocular surface alterations due to a number of predisposing factors.…”
Section: Discussionmentioning
confidence: 99%